Systems of Formation in Foucaults Archaeology: Incursion to Sub-Levels of Discourse (Global Journal of Medical Research, 2022)
Since the first undertakings carried out in its name in the 1960s, discourse analysis has shown itself to be a remarkably broad and diverse investigative field. In its french tendency, we could possibly relate the hybridity of this field to the achievements of Michel Foucault, whose discursive theory owes its elaboration to the interest addressed by the philosopher towards debates brought about by encounters and confrontations that took place in the field of social and human sciences during the 20th century. However, Foucault's text The Archeology of Knowledge, which can be considered as a founding work regarding the French school of discourse analysis, constitutes its theoretical place positively apart from linguistic analysis and from the textual dimension of discourse. Therefore, to approximate to linguists the theoretical developments Foucault carries out in the Archeology of Knowledge, it seems convenient to recover some of the discussions which might have served as a condition for this text to be presented the way we know it today.
Keywords: structuralism the archeology of knowledge discourse analysis michelfoucault l#xE9; vi-strauss